FINDING THE OPTIMAL SOLUTION TO ALGORITHMIC PROGRAMMING ISSUES THROUGH GRAPHS (Academia Science Repository, 2023)
This article discusses the problem of finding the optimal solution to economic processes using mathematical modeling, specifically the linear programming problem, through graphical methods.